2017
DOI: 10.1111/jep.12722
|View full text |Cite
|
Sign up to set email alerts
|

A survey of clinicians regarding respiratory physiotherapy intervention for intubated and mechanically ventilated patients with community‐acquired pneumonia. What is current practice in Australian ICUs?

Abstract: Respiratory physiotherapy treatment varies for intubated patients with CAP. Further research is required to determine what is considered best practice for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 46 publications
(66 reference statements)
4
21
0
5
Order By: Relevance
“…In our study, the most preferred treatment among PTs was chest physiotherapy (54%) irrespective of the clinical case scenario. The results of our study are in accord with similar practices observed in the USA (19), Europe (20), Australia (21,22), the UK, Hong Kong (23), and Asia (8,24,25). Based on the previous literature, the findings suggest a moderate to strong evidence of the use of chest physical therapy in maintaining bronchial hygiene (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the most preferred treatment among PTs was chest physiotherapy (54%) irrespective of the clinical case scenario. The results of our study are in accord with similar practices observed in the USA (19), Europe (20), Australia (21,22), the UK, Hong Kong (23), and Asia (8,24,25). Based on the previous literature, the findings suggest a moderate to strong evidence of the use of chest physical therapy in maintaining bronchial hygiene (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are valuable as the first to our knowledge identifying UK critical care physiotherapy around physiotherapy use of ACT, which are consistent with those reported from other international settings both in terms of range of techniques used, and rationale [10,11,13], as well as recommendations laid out in previous European guidelines [15]. Furthermore they reflect recently published updated national UK guidelines on provision of intensive care services that state "Targeted airway clearance interventions should only be considered in selected patients when clinically indicated" [14].…”
Section: Discussionsupporting
confidence: 86%
“…Standard strategies to minimise secretion retention typically include suctioning and heated humidification [7]. Respiratory physiotherapy utilises additional airway clearance techniques (ACT) to manage focal secretion retention including manual and/or ventilator lung hyperinflation, patient positioning, and chest wall manual techniques [8][9][10][11]. These techniques may be supplemented by use of adjunctive therapies such as mucoactive agents for increased volume or tenacity of secretions [12].…”
Section: Word Count Introductionmentioning
confidence: 99%
See 2 more Smart Citations